Maternity and Paternity at Work : Law and Practice across the World. - Addati, Laura (International Labour Office, 2014)
This study reviews national law and practice on both maternity and paternity at work in 185 countries and territories including leave, benefits, employment protection, health protection, breastfeeding arrangements at work and childcare.